The Employment Effects of the Disability Education Gap in Europe - Maciej Albinowski; Iga Magda; Agata Rozszczypała (Institute of Labor Economics (IZA), 2023)
We investigate the role of education in creating employment opportunities for persons with disabilities across the European Union. We use the European Union Statistics on Income and Living Conditions (EU-SILC) for 2011-2019. We find that educational attainment is a major factor determining the probability of employment among persons with disabilities. In particular, the employment effects of tertiary education are much larger among persons with disabilities than among non-disabled people: that is, having a disability is a greater disadvantage for less educated than for better educated people. We provide evidence that the endogeneity of educational attainment does not drive these findings. We also uncover substantial heterogeneity in the role of education between countries. In more developed countries, the employment status of persons with disabilities is generally less dependent on their educational attainment. Overall, we estimate that 20% of the disability employment gap in the 25-34 age group can be attributed to the gap in education between individuals with and without disabilities.
Keywords: I26; I14; C21; 330; disability; employment; educational attainment; European Union